Answers

  • Brainly User
2014-09-04T13:34:10+05:30
Sn=3n2+5n
so , s1=3*1*2+5*1
          =11
      s2=3*2*2+5*2
          =22
       s3=3*3*2+5*3
          =33
s1=t1=11
s2=t1+d=22
    =   d=22-11
           =11
d=11
AP:- 11,22,33
0
2014-09-04T13:37:55+05:30
Given that, 

S_n = 3n^2 + 5n

We know that,

t_n = S_n - S_(n-1)

t_n = 3n^2 + 5n - [3(n-1)^2 + 5(n-1)]

t_n = 3n^2 + 5n - [3n^2-6n+3 + 5n-5]

t_n = 3n^2 + 5n - 3n^2 + 6n - 3 -  5n + 5

t_n = 6n + 2

The series is 

6(1) + 2, 6(2)+2, 6(3)+2, 6(4)+2
⇒ 8, 14, 20, 26 ........
0